Colony defense behavior of the primitively eusocial wasp, mischocyttarus cerberus is related to age - Togni, Olga Coutinho [UNESP]; Giannotti, Edilberto [UNESP] (Oxford University Press (OUP), 2010)
The colony defense behavior of the wasp Mischocyttarus cerberus Richards (Hymenoptera, Vespidae) was studied to verify whether there were different reactions of wasps of different ages and hierarchical positions during attacks of ants. Detailed nest mapping was first performed, then the wasps were marked and were divided in four distinct categories: queens, older workers, younger workers and males. Tests were made simulating attacks of ants in the nests. The main results showed that the M. cerberus behaviors against ant attacks is more related to the age of the wasps than to their hierarchical position. The oldest wasps (queens and older workers) defend the nest more than the younger workers and males, representing a form of temporal polyethism.
Keywords: age polyethism; ethology; hierarchical position